2013
DOI: 10.1038/aps.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nicotine exposure enhances the susceptibility to metabolic syndrome in adult offspring rats fed high-fat diet via alteration of HPA axis-associated neuroendocrine metabolic programming

Abstract: Aim: Prenatal nicotine exposure (PNE) alters the hypothalamic-pituitary-adrenocortical (HPA) axis-associated neuroendocrine metabolic programming in intrauterine growth retardation offspring rats. In this study we aimed to clarify the susceptibility to metabolic diseases of PNE offspring rats fed a high-fat diet. Methods: Maternal Wistar rats were injected with nicotine (1.0 mg/kg, sc) twice per day from gestational day 11 until full-term delivery, and all pups were fed a high-fat diet after weaning and expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Excessive GCs in fetal circulation are believed to induce abnormal fetal development (such as IUGR) and result in potential diseases in adulthood (24). Our previous studies (27,35,71) reported that PNE could induce a metabolic disorder of glucose and lipid through fetal overexposure to maternal GCs. However, it is still unclear how GCs plays its role in the programming effects of adult hypercholesterolemia.…”
Section: Gc-igf1 Axis Might Mediate Programming Changes Of Pne-inducementioning
confidence: 99%
See 1 more Smart Citation
“…Excessive GCs in fetal circulation are believed to induce abnormal fetal development (such as IUGR) and result in potential diseases in adulthood (24). Our previous studies (27,35,71) reported that PNE could induce a metabolic disorder of glucose and lipid through fetal overexposure to maternal GCs. However, it is still unclear how GCs plays its role in the programming effects of adult hypercholesterolemia.…”
Section: Gc-igf1 Axis Might Mediate Programming Changes Of Pne-inducementioning
confidence: 99%
“…Moreover, the suppression of fetal adrenal function could be programmed and last into adulthood (75,76), which may account for the low GC level in male adult offspring rats in this study. Meanwhile, an unconstrained hepatic IGF1 pathway promoted catch-up growth (35) and accelerated cholesterol synthesis and output by increasing the expression of related genes. Taken together, GC-IGF1 axis programming was involved in PNE-induced increased hepatic cholesterol synthesis and output and contributes to the development of hypercholesterolemia in male adult offspring rats.…”
Section: Gc-igf1 Axis Might Mediate Programming Changes Of Pne-inducementioning
confidence: 99%
“…17 In our previous study, we confirmed that prenatal nicotine exposure might result in IUGR and maternal glucocorticoid (GC) over-exposure. 20,21 In brief, with an over-exposure to maternal GC, the development of the fetal HPA axis of the IUGR fetus was inhibited. 20,21 In brief, with an over-exposure to maternal GC, the development of the fetal HPA axis of the IUGR fetus was inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy stress such as pregnancy-induced hypertension, preeclampsia, malnutrition, chronic anemia and other adverse environmental stimuli lead to imbalances in the nutritional needs and supply of the fetus, resulting in IUGR, metabolism and endocrine adaptive changes [5]. These changes lead to abnormalities in the hypothalamic-pituitary-adrenal axis (HPA) [6], [7] and subsequently in metabolism and the endocrine, behavioral and cardiovascular systems. We screened GC-related genes in IUGR rat brain tissues with the Affymetrix Rat Gene 2.0ST chip and found that the expression of glucocorticoid receptor (GR or nuclear receptor subfamily 3, group C, member 1, GR, Nr3c1) and the receptor pre-regulatory enzyme 11β-hydroxysteroid dehydrogenase 2 (11β-HSD2) were significantly higher than those of normal rats, suggesting that GCs are abnormal in IUGR rats [8], [9].…”
Section: Effects Of Glucocorticoids (Gcs) On Infants With Iugrmentioning
confidence: 99%